1974
DOI: 10.1007/bf00389324
|View full text |Cite
|
Sign up to set email alerts
|

IAA transport during the phototropic responses of intact Zea and Avena coleoptiles

Abstract: Transport of indolyl-3-acetic acid (IAA) was studied during the phototropic responses of intact shoots and detached coleoptiles of Zea mays L. and Avena sativa L. The use of a high specific activity [5-(3)H]IAA and glass micropipettes enabled asymmetric application of the IAA to be made to individual coleoptiles with minimal tissue damage.A unilateral stimulus of 2.59×10(-11) einstein cm(-2) of blue light, probably in the dose range of the first positive phototropic response, caused significant net lateral mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Related to this model, Naqvi (1972) proposed that light-induced production of abscisic acid on the illuminated flank of the seedling causes unequal polar auxin transport. To test the idea that unequal polar auxin transport gives rise to phototropism, Gardner et al (1974) followed radiolabeled auxin that had been asymmetrically applied to coleoptiles. Although they were not able to completely exclude a role for light-mediated inhibition of polar auxin transport, their results further demonstrated that unilateral blue light induced lateral auxin transport.…”
Section: The Discovery Of Auxin and Understanding Its Role In Phototrmentioning
confidence: 99%
“…Related to this model, Naqvi (1972) proposed that light-induced production of abscisic acid on the illuminated flank of the seedling causes unequal polar auxin transport. To test the idea that unequal polar auxin transport gives rise to phototropism, Gardner et al (1974) followed radiolabeled auxin that had been asymmetrically applied to coleoptiles. Although they were not able to completely exclude a role for light-mediated inhibition of polar auxin transport, their results further demonstrated that unilateral blue light induced lateral auxin transport.…”
Section: The Discovery Of Auxin and Understanding Its Role In Phototrmentioning
confidence: 99%
“…1) caused by IAA (treatment in situ). It is well established that the movement of endogenous auxin is basipetal in coleoptiles (8) and acropetal in roots (20), consequently polar (3, 9, II). For exogenous IAA, the present data indicated a similar situation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Curry (1969) measured these and reported that the rate of growth of the dark side was 4-5 fold higher than the lighted side. Although Curry (1969) pointed out that these were much higher than the auxin differences which had been measured-very much so when considering the 0-15% lateral redistribution of Gardner et al (1974)-he failed to draw the obvious conclusion that they could not account for unequal growth. The problem is exacerbated when, as will be considered later, the evidence favours a logarithmic dose-response relation between auxin and extension, and auxin and curvature.…”
Section: The Essential Failure Of the Cholodny-went Theory To Explainmentioning
confidence: 95%
“…(We shall return to this paper later.) In a critical and penetrating reassessment of these experiments, Gardner et al (1974) solved many of the difficulties in earlier work. They micro-injected labelled indoleacetic acid asymmetrically into the tip of intact coleoptiles.…”
Section: The Essential Failure Of the Cholodny-went Theory To Explainmentioning
confidence: 98%